2021
DOI: 10.3390/ijerph182211907
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Preschool-Aged Children’s Movement Behaviors in Hong Kong: A Longitudinal Analysis of Accelerometer-Measured Data

Abstract: During the COVID-19 pandemic, many preschool-aged children were forced to remain indoors due to social distancing measures and school closures. In this study, we examined how children’s movement behaviors (sedentary behaviors, physical activity, and sleep) were affected by the pandemic. Children’s (N = 25, age = 4.4 years, SD = 0.3) movement behaviors were measured before and after the COVID outbreak, respectively. Data collected using accelerometers were analyzed using compositional data analyses. A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
5
14
1
Order By: Relevance
“…In the present study, weekly playtime was reduced while weekly sleep remained unchanged. These observations are in agreement with parent-reported data by researchers in another study who studied physical activity and sleep among preschoolers living in Hong Kong, but is also contrasted with accelerometer-derived physical activity and sleep data in the same group of 25 preschoolers [ 21 ]. The similarities and differences between the two studies could plausibly be explained by the different contexts between the countries before and during the COVID-19 pandemic, and the use of questionnaires versus accelerometers to obtain physical activity and sleep data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, weekly playtime was reduced while weekly sleep remained unchanged. These observations are in agreement with parent-reported data by researchers in another study who studied physical activity and sleep among preschoolers living in Hong Kong, but is also contrasted with accelerometer-derived physical activity and sleep data in the same group of 25 preschoolers [ 21 ]. The similarities and differences between the two studies could plausibly be explained by the different contexts between the countries before and during the COVID-19 pandemic, and the use of questionnaires versus accelerometers to obtain physical activity and sleep data.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that not all the studies show similar results. While parent reports suggest that preschool children were less physically active, slept less, and spent more time being sedentary, Ng et al (2021) reported that preschool children increased MVPA by 16%, spent 8% more time sleeping, and spent 9% less time engaging in sedentary behaviors—assessed using an accelerometer—during the COVID-19 pandemic than before [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since LPA may be important for students’ academic outcomes [ 26 ], future research should seek to improve elementary and middle school students’ LPA when not in school settings. Alternatively, preschoolers’ LPA changes were not significant, but their weekday LPA remained about the same, which is in line with another study that found no change in preschoolers’ LPA from pre- to early-pandemic [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…According to another systematic review and meta-analysis during the COVID-19 pandemic children’s inactive time increased by 159 min per day [ 14 ]. However, not all previous studies have reported a negative impact of the COVID-19 pandemic on children’s PA. Few studies have found that PA levels in children and adolescents increased during the COVID-19 pandemic compared with pre-pandemic levels [ 15 , 16 , 17 ]. Among Saudi adults, self-reported data showed that 52% of the study sample ( n = 2255) reported a decrease in their daily PA during the COVID-19 pandemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%